Carbon and oxygen stable isotope record of upper Kimmeridgian shallow-marine ramp carbonates (Iberian Basin, NE Spain): the imprint of different burial and tectonic histories - Cristina Sequero; Giovanna Della Porta; Beatriz Bádenas; Marcos Aurell (Geologica Acta, 2021)
Bulk carbon and oxygen stable isotopes of ancient shallow-marine carbonates can record the effects of multiple palaeoenvironmental factors, but also the imprint of several post-depositional processes, which may alter the original marine isotopic composition. In this study, carbon and oxygen stable isotope analyses were performed on bulk carbonate, bivalve calcitic-shell (Trichites) and calcite vein samples from two stratigraphic sections (Tosos and Fuendetodos, present-day distance 15km), representing proximal inner- and distal mid-ramp environments, respectively, of the uppermost Kimmeridgian ramp facies deposited in the northern Iberian Basin (NE Spain). These successions underwent different diagenetic pathways that altered the primary marine isotopic composition in each section in different ways. Different burial histories, tectonic uplift and a variable exposure to meteoric diagenesis from the end of the Kimmeridgian to the Cenozoic (following Alpine tectonic uplift) are reflected in the different alteration patterns of the carbon and oxygen stable isotope signatures. A significant deviation to lower values in both δ13O and δ18O is recorded in those carbonates mostly exposed to meteoric diagenesis (distal mid-ramp Fuendetodos section), because of post-depositional tectonic uplift (telogenesis). On the other hand, the deposits mainly affected by burial diagenesis (proximal inner-ramp Tosos section) only record low δ18O with respect to expected values for pristine Kimmeridgian marine carbonates. The different burial and tectonic uplift histories of these deposits in each sector, due to their different tectonic evolution in this part of the basin, resulted in a variable degree of diagenetic resetting. However, in spite of the different diagenetic resetting reported of the carbon and oxygen stable isotope signatures in each section, these carbonates show similar cement types in terms of fabrics and cathodoluminescence properties. The diagenetic resetting reported for these carbonates prevents the use of the δ13O and δ18O records for addressing palaeoenvironmental interpretations, but instead highlights useful features regarding the variable diagenetic overprint of the studied shallow-marine carbonate successions concerning their specific post-depositional history.